Valorization of almond agro-industrial residues: production of biopolyols from almond shell - Pinto, João Alves (2015)
The almond is a nut, well-known and quite produced in Portugal, especially in the region of Trás-os-Montes e Alto Douro and Algarve. Almond (Prunus dulcis) is a mid-size tree of the Rosaceae family (rose family). Almond fruit consists of the hull, shell, and kernel (nut). The edible kernel or nut is separated and collected for commercial uses and is widely used for food applications purposes. At global level almond production and processing generates millions of tons of residues in addition to almond nuts. Almond residues, including shells, hulls, pruning, leaves, skin and discharged inedible kernel, are viable feedstocks for a wide range of products. In this context, this work aims at review the uses of almond processing residues and related industries (e.g. sweet almond oil extraction) and open new avenues for their exploitation by suggesting new applications. The work comprises the identification and evaluation of the almond industry residues, their characterization and traditional uses. Additionally novel utilizations are proposed in the field of chemicals and materials. A special emphasis is given to the development of biopolyols from the almond shell by means of oxypropylation processes. In this last case, conventional synthesis using a high pressure reactor was attempted. The almond shell residue used in this work was characterized in what concerns lignocellulosic composition, moisture, ash contents and extractables. It comprises cellulose, hemicellulose and lignin at contents of 30.2%, 12.3% and 34.5%, respectively. Moreover it presents a moisture content of 6.0%, 2.2% of ashes and 8.1% of total extractables with predominance of the polar ones. Oxypropylation was successfully conducted under moderate conditions of temperature, pressure and time giving rise to liquid polyols with a homopolymer content ranging from 5-75%, a hydroxyl number between 250-520 mg KOH/g and viscosities up to 750 Pa.s. The unreacted almond shell residues varied between 5.0 and 37.3%, results in accordance with published data for other biomass substrates. In a general way it was observed that low AS/PO ratios (i.e. 10/90) give rise to polyols with low unreacted AS residue, low viscosity (due to a high homopolymer content), and the lowest IOH number. Moreover the polyols based on this formulation presented the highest thermal stability, especially the one with the formulation 10/90/5. The polyols based on the AS/PO ratio of 30/70 presented high unreacted AS residues, low homopolymer content, high IOH number (the highest value correspond to the formulation 30/70/5, 518.2 mgKOH/g) and high viscosity.